2019
DOI: 10.1186/s13020-019-0278-1
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of Chinese herbal medicine DAEP relieves the osteoarthritic knee pain in rats

Abstract: BackgroundThe potential adverse effects of conventional oral pharmacotherapy of osteoarthritis (OA) restrict their long-term use. Topical application of a Chinese herbal paste for relieving OA knee pain can be effective and safe. However, evidence-based scientific research is insufficient to support its application worldwide. The aim of this study was to investigate the in vivo efficacy of a topical Chinese herbal paste on relieving OA knee pain and its underlying mechanism.MethodsAn OA rat model was developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Our findings revealed that 5-Loxin caused a significant reduction in inflammatory responses and cartilage degradation in aMIA-induced OA model in rats. One measure of OA in rats is reduced HWD due to joint pain and stiffness [ 29 ]. HWD assesses the distribution of the pressure exerted by each hind paw.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings revealed that 5-Loxin caused a significant reduction in inflammatory responses and cartilage degradation in aMIA-induced OA model in rats. One measure of OA in rats is reduced HWD due to joint pain and stiffness [ 29 ]. HWD assesses the distribution of the pressure exerted by each hind paw.…”
Section: Discussionmentioning
confidence: 99%
“…Dipsacus asperoides, a traditional herbal medicine, has long been used in China and Korea for the treatment of bone diseases such as bone fracture, osteoporosis, and rheumatoid arthritis ( Wong et al, 2007 ; Gong et al, 2019 ). According to recent studies, Dipsacus asperoides has beneficial therapeutic effects on inflammation, osteoporosis, and joint disease ( Liu et al, 2016a ; Yue et al, 2017 ; He et al, 2019 ; Siu et al, 2019 ). However, the effects of Dipsacus asperoides on OA have not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports show that Dipsacus asperoides has a substantial antirheumatic effect on collagen-induced arthritis in mice ( Jung et al, 2012 ) and an osteoprotective effect in ovariectomized rats ( He et al, 2019 ; Sun et al, 2019 ). In addition, Chinese herbal medicine paste containing Dipsacus asperoides relieves osteoarthritic knee pain in rats ( Siu et al, 2019 ); these effects are related to the ethnopharmacological actions of the plant. However, the ethnomedicinal effects of Dipsacus asperoides on the joint disease osteoarthritis (OA) have not yet been reported, even though natural product research for OA is an area of active research.…”
Section: Introductionmentioning
confidence: 99%
“…For OA studies, Stand and Swing durations and Paw Print Area are commonly reported parameters measured by CatWalk in gait analysis [ 43 , 44 , 45 , 46 , 47 ]. For gait and pain sensitivity measurements, a biphasic response is reported in the literature, characterized by an early synovial inflammatory phase up to day 7, and a second chronic phase from day 14 corresponding to structural and degenerative alterations [ 48 ].…”
Section: Discussionmentioning
confidence: 99%